Interleukin-15 responses to acute and chronic exercise in adults: a systematic review and meta-analysis - Khalafi, Mousa; Maleki, Aref Habibi; Symonds, Michael E.; Sakhaei, Mohammad Hossein; Rosenkranz, Sara K.; Ehsanifar, Mahsa; Korivi, Mallikarjuna; Liu, Yubo (Frontiers in Immunology, 2024)
Interlukin-15 (IL-15) is an inflammatory cytokine that plays a vital role in immunology and obesity-associated metabolic syndrome. We performed this systematic review and meta-analysis to investigate whether exercise promotes circulating IL-15 concentrations in adults. We searched PubMed, Web of Science, and Scopus from inception to May, 2023 and identified original studies that investigated the effectiveness of acute and/or chronic exercise on serum/plasma IL-15 levels in adults. Standardized mean differences (SMD) and 95% confidence intervals (CI) were calculated using random effect models. Subgroup analyses were performed based on type of exercise, and training status, health status and body mass indexes (BMI) of participants. Fifteen studies involving 411 participants and 12 studies involving 899 participants were included in the acute and chronic exercise analyses, respectively. Our findings showed that acute exercise increased circulating IL-15 concentrations immediately after exercise compared with baseline [SMD=0.90 (95 % CI: 0.47 to 1.32), p=0.001], regardless of exercise type and participants’ training status. Similarly, acute exercise was also associated with increased IL-15 concentrations even one-hour after exercise [SMD=0.50 (95 % CI: 0.00 to 0.99), p=0.04]. Nevertheless, chronic exercise did not have a significant effect on IL-15 concentrations [SMD=0.40 (95 % CI: -0.08 to 0.88), p=0.10]. Our results confirm that acute exercise is effective in increasing the IL-15 concentrations immediately and one-hour after exercise intervention, and thereby playing a potential role in improving metabolism in adults.